A Hive Entrance System That Directs Honey Bees Inside or Outside a Greenhouse Reduced Colony Decline While Effectively Pollinating Zucchini Squash - Gomes, Cássia R. A. [UNESP]; Batista, Mateus A. M. [UNESP]; Ferraz, Yara M. M. [UNESP]; Trivellato, Matheus F. [UNESP]; Siniscalchi, Gustavo A. [UNESP]; Polycarpo, Gustavo V. [UNESP]; Rigobelo, Everlon C. [UNESP]; De Jong, David; Nicodemo, Daniel [UNESP] (MDPI, 2024)
Honey bee colonies rapidly decline when confined to greenhouses, increasing pollination rental costs as they need to be replaced frequently. We tested a hive system with entrances that can be manipulated to direct bees inside or outside greenhouses containing a zucchini crop. In one greenhouse, the bees could only forage inside for 15 days; in another, bees were directed to the inside from 5 to 9 a.m., after which they only foraged outside. This procedure was repeated two more times in each greenhouse with new hives. Data were collected on how the number of bee flower visits affected fruit production, the frequency of flower visits, and the amount of bee brood and food in the hives. Flowers visited by bees four times or more set more and larger fruit. The frequency of flower visits by bees from the hives confined to the greenhouse was reduced after eight days; it was not reduced in the greenhouse with bees that could forage outside. The bee brood area was reduced in the colonies that were confined to the greenhouse, while it was maintained in the semi-confined hives. The hives with controllable entrances proved effective for pollination, while causing less damage to the bees.
Keywords: brood; fruit set; honey; pollen; protected cultivation